(untitled) (Baghdad Science Journal, 2007)
This Study was conducted to investigate vaginitis in women who live in Baghdad City. Results Revealed that Candida spp. were the causal agent of 38.5% of symptomatic cases the yeasts Candidaalbicans, C.glabrata, C.tropicalis, C.parapsilosis and C.krusei were isolated with the percentage of 38.1, 9.1, 3.9, 2.6, 1.3 respectively also there were 18% of women in control group carrying Candida spp. The direct smear method were not efficient because the percentage of infection was 17.5% comparing with the culture method the sensitivity of direct smear method was 45.5% The percentage of WBC to Epithelial cells was less than one in 76.6% of women.